3(6-2x)+1=2(1x+2)-5x

Simple and best practice solution for 3(6-2x)+1=2(1x+2)-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(6-2x)+1=2(1x+2)-5x equation:


Simplifying
3(6 + -2x) + 1 = 2(1x + 2) + -5x
(6 * 3 + -2x * 3) + 1 = 2(1x + 2) + -5x
(18 + -6x) + 1 = 2(1x + 2) + -5x

Reorder the terms:
18 + 1 + -6x = 2(1x + 2) + -5x

Combine like terms: 18 + 1 = 19
19 + -6x = 2(1x + 2) + -5x

Reorder the terms:
19 + -6x = 2(2 + 1x) + -5x
19 + -6x = (2 * 2 + 1x * 2) + -5x
19 + -6x = (4 + 2x) + -5x

Combine like terms: 2x + -5x = -3x
19 + -6x = 4 + -3x

Solving
19 + -6x = 4 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
19 + -6x + 3x = 4 + -3x + 3x

Combine like terms: -6x + 3x = -3x
19 + -3x = 4 + -3x + 3x

Combine like terms: -3x + 3x = 0
19 + -3x = 4 + 0
19 + -3x = 4

Add '-19' to each side of the equation.
19 + -19 + -3x = 4 + -19

Combine like terms: 19 + -19 = 0
0 + -3x = 4 + -19
-3x = 4 + -19

Combine like terms: 4 + -19 = -15
-3x = -15

Divide each side by '-3'.
x = 5

Simplifying
x = 5

See similar equations:

| 0=4t+72 | | 1+-8z=-15 | | -y+6=11 | | 12x+5x=13x | | 2x-(x-5)=7-6(x-2) | | 48-6x=4x | | 5x+6y=6y+5x | | (9/10)*(4/5) | | -5x=4y+8 | | n+6=-16 | | 6s+s-4s-3s+4s=16 | | X^2+y^2+3x-2y=0 | | 5=3-(4-2) | | -4j-3j-j+j=20 | | 23=w+6 | | 1-2tan^2x=-tan^2x | | 0.25(y-4)+.03y=0.18y-0.05(40) | | j+j-j=11 | | -16t^2+84t+112=0 | | 6.3/0.9-(-4.1)x(-0.4) | | 8y-2(5+2y)=7y-16 | | 2 = 12(9x+8) | | -3(3x-3)-9=-2(7x+3)-3 | | 16t^2+84t+112=0 | | 3x+6=27+y | | 7y+-42x+7=0 | | -8-6=7x-2-6x | | 6x-(8X+9)=2x-17 | | 9x+16y=-2 | | Sqrtx^2+7=x+1 | | 5*(x+8)=110 | | 26-u=234 |

Equations solver categories